Studi Uji Kuat Tekan Uniaksial dan Uji Kuat Tarik Tidak Langsung Untuk Menentukan Brittleness Index (BI) Pada Batupasir di Formasi Pulau Balang dan Balikpapan - Musmulyanas Mus; Tommy Trides; Lucia Litha Respati (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
In the process of designing mine slopes, drilling or tunneling, to determine the level of strength and brittleness factors of rock on a slope, it is necessary to carry out a uniaxial compressive strength test or indirect tensile strength test of the rock. Compressive strength testing is carried out to determine how long the rock maintains its strength or elastic properties when pressure is applied. This data can be used as information to understand the analysis of factors that influence the physical properties of rocks on the compressive strength of rocks from physical properties and compressive strength testing activities. and indirect tensile strength testing is carried out to determine the stress value contained in the rock. To determine the level of rock brittleness, it can be done by comparing the uniaxial compressive strength value and the indirect tensile strength value. This data can be used as information and reference for companies that will design a mine slope, drill and tunnel, how strong the strength and level of brittleness of rocks in areas dominated by sandstone. This research uses quantitative methods, so that to obtain accurate calculation data, testing methods are used in the form of uniaxial compressive strength tests and indirect tensile strength tests, in this case tested on sandstone samples obtained from 2 rock formations including the Pulaubalang formation and the Balikpapan formation, so that accuracy The test result values ​​can be obtained well. And after testing, a comparison is made between the uniaxial compressive strength test value and the indirect tensile strength test to obtain the Brittleness Index value.Based on the observation results, it can be concluded that when the brittleness of the rock becomes greater, the performance of the cutting digger increases several times.